The Influence of Ethics, Leadership as a Driver of Educational Innovation and its Impact on Student Performance - Aini, Nur; Putri, Kirana Utami; Paradipa, Paradipa; Rahayu, Nurmala Anggun (Indonesian Educational Administration and Leadership Journal (IDEAL), 2025)
This study investigates the influence of ethical leadership on educational innovation and its impact on student achievement in secondary schools. By applying the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, this study involved 61 teachers and 160 students as participants in the study. The findings of the study indicate that ethical leadership can create a collaborative and inclusive learning environment, which also encourages innovation in education. A high level of teacher ethics has a positive impact on the formation of student character, increasing their motivation, and better academic performance. This study emphasizes the importance of combining ethical leadership with educational innovation to create a learning environment that can adapt to changing times. The theoretical and managerial impacts of this study provide guidance in the development of effective education policies, especially in improving the quality of education in developing countries. Keywords: word, ethic, leadership, innovation, performance, educational